Regionalizm jako wielopłaszczyznowa forma podtrzymywania kultury lokalnej i języka: uwagi do lektury „Nowego bedekera kaszubskiego” Tadeusza Bolduana - Puppel, Stanisław (Studia Rossica Posnaniensia, 2018)
In this paper, the view is proposed that human culture appears fundamental in resolving the problem of ‘the human condition’. Its holistic nature comprises all tangible and intangible aspects, including artefacts, language and communication. It is the culture-language complex which is responsible for the generation of both collective and individual human identity via its locality expressed in a plethora of tangibleintangible manifestations. The regionalism of this complex ought to result in special care of both institutions and individuals who, by demonstrating active involvement on a local scale, are co-responsible for the maintenance of local cultural-linguistic identity. Its vitality is, in turn, more than significant for the maintenance of identity on a larger (e.g. national, global) scale. The aforementioned aspects of regionalism are discussed here on the basis of a review of the content of an encyclopedic outline of Kashubian culture (Bedeker) authored by Tadeusz Bolduan.